Aristotelian Rhetoric and Arabic Balāghah in Teaching Arabic as a Foreign Language: A Conceptual Comparative Study - Muhammad Dhiya’ Syaifullah; Kamal Yusuf; Sovia Fahraini (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the conceptual relationship between Aristotelian rhetoric and Arabic balāghah within the context of Teaching Arabic as a Foreign Language (TAFL), with a particular focus on speaking skills (maharah al-kalām). Using a conceptual comparative approach, the study analyzes primary rhetorical texts and relevant secondary literature to identify differences in epistemological orientation, rhetorical mechanisms, and pedagogical implications. The findings reveal that Aristotelian rhetoric is grounded in rational–pragmatic persuasion, positioning language as an instrument to influence audiences, whereas Arabic balāghah is oriented toward the appropriateness of meaning and context, viewing language as a system of contextualized meaning. These differences result in distinct approaches to speech design, rhetorical evaluation, and assessment in TAFL. The study argues that uncritical adoption of Aristotelian rhetorical frameworks risks neglecting the language-specific and contextual nature of Arabic rhetoric. Consequently, it proposes an integrative pedagogical perspective that combines the structural strengths of Aristotelian rhetoric with the linguistic–pragmatic foundations of Arabic balāghah to enhance the teaching of Arabic speaking skills.